2000
DOI: 10.1136/fn.82.3.f243
|View full text |Cite
|
Sign up to set email alerts
|

Changes in pulmonary arterial pressure in preterm infants with chronic lung disease

Abstract: Background-Pulmonary arterial pressure (PAP) is raised in preterm infants with respiratory distress syndrome who subsequently develop chronic lung disease. The natural history of pulmonary hypertension in infants with chronic lung disease is unknown. Objectives-To investigate changes in PAP, assessed non-invasively using Doppler echocardiography, in infants with chronic lung disease during the 1st year of life. Methods-Serial examinations were performed in infants with chronic lung disease and healthy preterm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
47
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(51 citation statements)
references
References 28 publications
2
47
2
Order By: Relevance
“…Despite striking changes in the nature and epidemiology of BPD over the past decades, PH continues to contribute significantly to high morbidity and mortality in BPD and can occur early in the course of disease. 259,260 Original descriptions of BPD reported striking pulmonary hypertensive vascular remodeling in severe cases and that the presence of PH beyond 3 months of age was associated with a high mortality rate (40%). 261 In the postsurfactant era, late PH continues to be strongly linked with poor survival in the "new BPD."…”
Section: Bronchopulmonary Dysplasiamentioning
confidence: 99%
“…Despite striking changes in the nature and epidemiology of BPD over the past decades, PH continues to contribute significantly to high morbidity and mortality in BPD and can occur early in the course of disease. 259,260 Original descriptions of BPD reported striking pulmonary hypertensive vascular remodeling in severe cases and that the presence of PH beyond 3 months of age was associated with a high mortality rate (40%). 261 In the postsurfactant era, late PH continues to be strongly linked with poor survival in the "new BPD."…”
Section: Bronchopulmonary Dysplasiamentioning
confidence: 99%
“…Recent data from human infants with bronchopulmonary dysplasia (BPD), a chronic neonatal lung injury that affects preterm infants, have demonstrated structural remodeling of pulmonary resistance arteries as early as 2 wk after birth (30). These data provide a pathological correlate for recent echocardiographic studies demonstrating raised pulmonary arterial resistance in infants with BPD (27,28), which together indicate that pulmonary hypertension remains a common manifestation of this condition.…”
mentioning
confidence: 82%
“…In the postsurfactant era, a limited number of studies have shown that severe pulmonary hypertension in BPD patients is related to decreased survival, and high pulmonary arterial pressures persist until the end of the first year, but not until 7-8 years of age [3,4,5]. Neither the duration nor the significance of echocardiographic changes is clear in new BPD patients, and we do not know whether there are risk factors that can be avoided to prevent cardiac sequelae in this group of patients.…”
Section: Introductionmentioning
confidence: 99%